Final answer:
To convert y + 2 = 7(x - 1) to slope-intercept form, expand and rearrange to solve for y, resulting in y = 7x - 9, which is option A.
Step-by-step explanation:
The student's question is to convert the equation y + 2 = 7(x - 1) into slope-intercept form, which is y = mx + b. To do this, first expand the right side of the equation:
y + 2 = 7x - 7
Next, subtract 2 from both sides of the equation to solve for y:
y = 7x - 7 - 2
Combine like terms:
y = 7x - 9
So the equation in slope-intercept form is y = 7x - 9, which corresponds to option A.